ANALYSIS OF STUDENT RESPONSES IN LEARNING WITH ANDROID-BASED MEDIA - Falasifah Hasyim Chosi; Malia Fransisca (UIR Press, 2020)
The author will try to do research by developing android-based interactive learning media on BTA learning materials, the author wants to try to find out the response of UIN SAIZU students to the learning media. This study aims to determine student responses to android-based interactive learning media at UIN SAIZU by using the observation method and learning test results. Data collection teaching. The results of the study were obtained based on the results of students’ responses to learning media based on Android on BTA material getting an average percentage of 78.21% in the first observation test with good categories and observation test. The research will try to prove that Android-based BTA learning is very effective because it can be used for all circles, both students and people who are very busy because learning can be done anywhere besides being practical, Android can be used for all positive things. conclusions can be drawn from this discussion as follows: Applications for learning tajwid based on android can be used by Muslims as an alternative to learning tajwid independently. With the application of learning tajwid which is equipped with examples of images and sounds, as well as quizzes to test abilities, users are expected to be able to maximize this mobile application as a medium for learning tajwid that is easy to use and easy to reach. Tajweed science applications can be run via smartphones with the Android operating system. The application of tajwid is made using the Java programming language and designed with an easy display.